Modern Education in Science, Values, and Technology - Turdiyev Shokhrukh Razzakovich; D. O. Shokirova (Scientific Trends, 2025)
This article emphasizes that today’s students are required not only to be specialists in their field, but also to possess broad knowledge — including historical, psychological, pedagogical, political, and economic literacy, as well as information management skills. The main goal of updating the content of education is to shape individuals who can think critically, are independent, cultured, well-rounded, and capable of expressing their thoughts freely.
Keywords: Education, technology, informatization, values, science, qualification, specialist.